4(3x-2)-5x=6-(2x-1)

Simple and best practice solution for 4(3x-2)-5x=6-(2x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3x-2)-5x=6-(2x-1) equation:


Simplifying
4(3x + -2) + -5x = 6 + -1(2x + -1)

Reorder the terms:
4(-2 + 3x) + -5x = 6 + -1(2x + -1)
(-2 * 4 + 3x * 4) + -5x = 6 + -1(2x + -1)
(-8 + 12x) + -5x = 6 + -1(2x + -1)

Combine like terms: 12x + -5x = 7x
-8 + 7x = 6 + -1(2x + -1)

Reorder the terms:
-8 + 7x = 6 + -1(-1 + 2x)
-8 + 7x = 6 + (-1 * -1 + 2x * -1)
-8 + 7x = 6 + (1 + -2x)

Combine like terms: 6 + 1 = 7
-8 + 7x = 7 + -2x

Solving
-8 + 7x = 7 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-8 + 7x + 2x = 7 + -2x + 2x

Combine like terms: 7x + 2x = 9x
-8 + 9x = 7 + -2x + 2x

Combine like terms: -2x + 2x = 0
-8 + 9x = 7 + 0
-8 + 9x = 7

Add '8' to each side of the equation.
-8 + 8 + 9x = 7 + 8

Combine like terms: -8 + 8 = 0
0 + 9x = 7 + 8
9x = 7 + 8

Combine like terms: 7 + 8 = 15
9x = 15

Divide each side by '9'.
x = 1.666666667

Simplifying
x = 1.666666667

See similar equations:

| 3(x-2)=-36-7x | | .5b+4=2+3d-.5 | | 2x+10=x-6 | | -97=6(3n-2)-n | | 2p-2(6-2p)=2(p-5)-2 | | -3n-16=7(n+2) | | -3(4x-15)-8(3x-5)= | | 5d-2-d= | | -4y-8y=-15 | | 9x=9x+18 | | 9y=-1 | | 35+8r=7(2r-1) | | 5x-6=5x-x | | 6-x=-24 | | 3w-5-19w^2+17= | | 8(v+1)-4v=2(2v+2)-8 | | -5(1-5x)=-8x-5 | | 3+25+15x=58 | | 8y+4-6y=7+y-6 | | 2.4p-5=9.4 | | -6v-5(v+5)=-6v-5 | | 6-3x=5x-10x+4+2 | | 23=x^2+7 | | 13x+8x=3x-2 | | 8n+48=48+8n | | 6x+6=p | | -38-8n=-8(n+6)+2n | | y(5y^2+9)-2(7y-6y^3)= | | .2c+.286=2-.143c | | -6+2a=-6(a+5) | | -3(8x-27)-2(x+19)= | | -32+3r=7-4(7r+2) |

Equations solver categories